FINANCING DETERMINANT OF NATURAL CERTAINTY CONTRACTS (NCC) AND NATURAL UNCERTAINTY CONTRACTS (NUC) ON PROFITABILITY OF ISLAMIC COMMERCIAL BANKS - Milzam, Mardas; Siswanto, Siswanto (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Commercial banks have a significant role for the society to fill its financial needs through financing facilities. Islamic bank financing has two forms of contracts, namely financing for Natural Certainty Contracts (NCC) and financing for Natural Uncertainty Contracts (NUC). Those are able to improve the profitability of Islamic commercial banks. The purpose of this study is to analyze the impact of NCC financing and NUC financing contracts toward the improvement of the Islamic commercial banks’ profitabilities represented by Return On Asset (ROA). This study uses a quantitative approach. The data analysis uses panel regression analysis with software Eviews 9.0 tools. Sampling method uses purposive sampling of Islamic Commercial Banks of 2013-2017. Result of the study showed that NCC and NUC variables improved the profibility of commercial banks simultaneously. Meanwhile, the test results partially showed that the NCC variable has a significant positive effect on the profitability of Islamic commercial banks. NCC financing has a fixed and definite return characteristic, was used for short-term investment financing, and the mark-up of profits could be adjusted, and the bank did not interfere with the customer’s business. NUC financing variable showed a significant negative effect on the profitability of Islamic commercial banks in a conventional manner. The high risk of banks in financing with NUC will be the negative impact factor. The risks borne by the banks include three factors, namely: there is bad financing due to side streaming, changes in management of customer management, and the existence of asymmetric information in customer financial reporting.